PENGGUNAAN PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN KARAKTER PEDULI LINGKUNGAN SISWA KELAS 3 SDN 2 SINDANGKASIH PADA MATA PELAJARAN PENDIDIKAN LINGKUNGAN HIDUP - Rahma, Ayang Ranisa; Aghniyah, Isna Alifia; Trsinawati, Puput; Muharam, Agus; Mustikaati, Wina (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
This study aims to describe the implementation of Environmental Education learning at the elementary school level, as well as to determine whether there is an increase in students' environmental awareness through Environmental Education with a Contextual Learning Approach, in which this approach links between the content of subject matter and real-life situations from oneself. students to build relationships between the knowledge they have and their daily lives. This research is a qualitative research with a type of field study and literature study. And using Classroom Action Research which is designed in one cycle consisting of 4 stages. Data collection techniques used are interviews, observation and documentation. The results of the research show that the learning of Environmental Education at SDN 2 Sindangkasih is implemented quite well. As for its implementation, Environmental Education takes an important role that influences the character of students.